Fasting plasma homocysteine as a sensitive parameter of antifolate effect: a study of psoriasis patients receiving low-dose methotrexate treatment - Refsum, H; Helland, S; Ueland, P M (Clinical pharmacology and therapeutics, 1989)
We have investigated the effect of low-dose methotrexate (25 mg weekly) on plasma homocysteine in 13 patients who had psoriasis. Total, free, and protein-bound homocysteine were determined both during fasting and after methionine loading. Psoriasis patients had significantly higher basal plasma homocysteine levels than age-matched control subjects. In addition, the methionine loading test was abnormal in four of the patients, but this was not significant. Psoriasis patients, although not folate deficient, did have lower serum folate levels than control subjects. There was a significant and transient increase in fasting plasma homocysteine levels within 48 hours after administration of low-dose methotrexate. This response was repeated after each administration and was observed eight to 20 times in three patients whose progress was monitored for 2 to 6 months. Notably, methotrexate did not affect the plasma profile for homocysteine after methionine loading. This study showed the level of fasting plasma homocysteine to be a sensitive and responsive parameter of antifolate drug treatment.